1983
DOI: 10.1159/000153345
|View full text |Cite
|
Sign up to set email alerts
|

The Inter- and Intra-Tribal Distribution of Red Cell G6PD Phenotypes in Sudan

Abstract: 1,416 males and 564 female subjects from four Negroid and five Arab tribes and a group of mixed tribes of the Sudan were investigated for the phenotypic distribution of red cell glucose-6-phosphate dehydrogenase by starch gel electrophoresis. In general, the tribes of Negroid origin had higher frequency of GdA compared to the tribes of Arab ancestry. However, the Nilotes showed a lower frequency of GdA allele and the Mahass tribe claiming an Arab origin had a higher frequency of GdA<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
1

Year Published

1985
1985
2010
2010

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 2 publications
3
4
1
Order By: Relevance
“…The frequency of GdA was found to be very low (0.026 and 0.007) in both Bedouins and non-Bedouin Arabs of Jordan, which con firms our earlier observation. A similar low frequency of GdA has been reported in Saudi Bedouins (0.02) [Bayoumi et al, 1979;Samuel and Saha, unpublished] and North Sinai Bedouins (0.015) , A much higher frequency of GdA was reported in Sudanese Arabs [Saha et al, 1978[Saha et al, , 1983; and in a city population of North Sinai (0.045) . The frequency of Get in the present population was observed to be 0.069 in Bedouins and 0.047 in non-Bedouins, respectively, which is slightly higher than that observed in our earlier series of Jordanians (0.032) [ Banerjee et al, 1981].…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…The frequency of GdA was found to be very low (0.026 and 0.007) in both Bedouins and non-Bedouin Arabs of Jordan, which con firms our earlier observation. A similar low frequency of GdA has been reported in Saudi Bedouins (0.02) [Bayoumi et al, 1979;Samuel and Saha, unpublished] and North Sinai Bedouins (0.015) , A much higher frequency of GdA was reported in Sudanese Arabs [Saha et al, 1978[Saha et al, , 1983; and in a city population of North Sinai (0.045) . The frequency of Get in the present population was observed to be 0.069 in Bedouins and 0.047 in non-Bedouins, respectively, which is slightly higher than that observed in our earlier series of Jordanians (0.032) [ Banerjee et al, 1981].…”
Section: Resultssupporting
confidence: 75%
“…A similar low fre quency of Gd' has been reported in the Bedouin Arabs of Saudi Arabia (0.02 and 0.05), and in Sudanese Arabs (0.03) [Bayoumi et al, 1979;Saha et al, 1983]. A somewhat higher frequency of Gd' (up to 0.08) was reported among the Bedouins of North Sinai , The rare hyperactive and slow-moving variant G d b(krt) originally detected among the Sudanese [Saha et al, 1978[Saha et al, , 1983 was not present in our earlier series of Jordanians. A low frequency of this allele was present in both groups.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…However, the frequency of this hyperactive Gd var iant has been found to be lower in the present series. The same allele had been detected in Jordanians [24] and in the Ni lotic, Negroid and Arab tribes of Sudan [25]. However, this new Gd allele is not as sociated with any haemoglobinopathies and as such no selective advantage is ex pressed.…”
Section: Red Cell G6pd Phenotypes In Relation To Haemoglohinopathiesmentioning
confidence: 57%
“…A more detailed electrophoretic study o f more than 2,000 Sudanese suggested that the Qjkhartoum varjant js not very uncomm on in the country [6], although less common than the G dA and deficient alleles (G dA~ and G dB"). The average activity of the QjKhartoum (n = 14) was foun(] to be signifi cantly higher (p < 0.001) than the common G d B variant [8].…”
Section: Introductionmentioning
confidence: 99%